Assessment and monitoring of land degradation using remote sensing and geographic information systems (GIS): a case study of Qoqodala within the Wit-Kei catchment in the Eastern Cape, South Africa - Ngcofe, Luncedo Dalithemba Sanelisiwe (Rhodes University, Faculty of Science, Department of Geography, 2009)
Land degradation is a global problem affecting many countries including South Africa. This study was conducted in order to assess and monitor the nature and extent of land degradation within Qoqodala in the Eastern Cape Province, of South Africa. The study used GIS and Remote Sensing techniques together with household interviews in determining extent, spatial characteristics and nature of land degradation within the study area. Vegetation cover and bare-ground change were the land degradation indicators assessed and monitored by this study. Through RGB band combination, Tasselled Cap Analysis and Unsupervised ISODATA classification techniques, Landsat images over the past eighteen years (1984, 1993, 1996, 2000 and 2002) have been analysed. The results showed that there is vegetation cover and bare-ground increase in the study area. The vegetation increase has been seen as a sign of land degradation increase due to the encroachment of indigenous vegetation by Euryops species (also known as Lapesi by the local community). The bare-ground land degradation indicator has also increased. The analyses of slope showed the spatial characteristics of bare-ground occurring on moderate to flat slopes while vegetation cover occurs on steep to very steep slopes. Furthermore the photographs captured during field visits show rills and gullies or dongas occurring on bare-ground. The interviewed respondents indicated that decline in food production, increase in dongas and vast increase in Euryops and a decline in grassland are the indicators of degradation that are observed in the study area. The occurrence of erosion features (rills and dongas) on bare-ground and the increase of vegetation shown by GIS and Remote Sensing techniques showed a positive correlation with field and household survey towards establishing the nature of land degradation. In this study Landsat images together with interviews proved to be a very useful tool for land degradation research. However the suggestion of a higher spatial resolution satellite image on small catchment studies is recommended
Keywords: Geographic information systems -- South Africa -- Eastern Cape; Remote sensing -- South Africa -- Eastern Cape; Land degradation -- South Africa -- Eastern Cape